Creative teaching approaches in reading for ESL learners and how it can empower ESL teachers' professional development - Ling, Sharon Jie Jing; Mohamed Ilias, Annur Alisa; Othman, Moomala; Ismail, Lilliati; Aralas, Dalia (Faculty of Educational Studies, Universiti Putra Malaysia, 2018)
Creativity is one of the approaches used for ESL learners and teachers. It aims to improve learners’ approaches of learning and to discover ESL teachers’ strength in teaching. Studies have shown that through creativity, it can help to improve ESL learners’ method of learning and to improve ESL teachers’ way of teaching. Reading will be our main focus. This paper will be highlighting or studying on the various creative approaches in the teaching of reading and their effectiveness in developing ESL proficiency among learners and also to empower ESL teachers’ professional development. Inclusive are the reasons for these approaches and when these approaches are used among ESL learners and teachers. Using various approaches will not only make communication more engaging, but also make learners more creative in learning, and also to increase ESL teachers’ strength in professional development, such as when it is done in teaching. This paper will provide teachers with a repertoire of reading skill approaches which will be helpful in developing ESL learners’ proficiency and empowering ESL teachers’ professional development.